Course development in IC manufacturing - Pineda de Gyvez, J. (IEEE transactions on education, 1994)
A traditional curriculum in electrical engineering separates semiconductor processing courses from courses in circuit design. As a result, manufacturing topics involving yield management and the study of random process variations impacting circuit behaviour are usually vaguely treated. The subject matter of this paper is to report a course developed at Texas A&M University, USA, to compensate for the aforementioned shortcoming. This course attempts to link technological process and circuit design domains by emphasizing aspects such as process disturbance modeling, yield modeling, and defect-induced fault modeling. In a rapidly changing environment where high-end technologies are evolving towards submicron features and towards high transistor integration, these aspects are key factors to design for manufacturability. The paper presents the course's syllabus, a description of its main topics, and results on selected project assignments carried out during a normal academic semester.< >